Cerebral Sinovenous Thrombosis - Ichord, Rebecca (Frontiers in Pediatrics, 2017)
Cerebral sinovenous thrombosis (CSVT) is a rare but serious cerebrovascular disorder affecting children from the newborn period through childhood and adolescence. The incidence is estimated at 0.6/100,000/year, with 30-50% occurring in newborns. Causes are diverse, and are highly age dependent. Acute systemic illness predominates risk factors among newborns. In childhood acute infections of the head and neck such as mastoiditis are most common, followed by chronic underlying disease such as nephrotic syndrome, cancer, and inflammatory bowel disease. Signs and symptoms are also age-related, with seizures and altered mental status the predominant manifestation in newborns, contrasted with headache, vomiting and lethargy, sometimes with 6th nerve palsy, the most common triad of symptoms in children and adolescents. Recent multicenter cohort studies from North American and Europe have provided updated information on risk factors, clinical presentations, treatment practices and outcomes. While systemic anticoagulation is the most common specific treatment used, there are wide variations and many uncertainties even among experts concerning best practice. The treatment dilemma is especially pronounced for neonatal CSVT, due in part to the higher prevalence of intracranial hemorrhage at baseline for newborns on the one hand, and the clear evidence that newborns suffer greater long-term neurologic morbidity on the other hand. With the advent of widespread availability and acceptance of acute endovascular therapy for arterial ischemic stroke, there is renewed interest in evaluating the role of this therapy for children with CSVT. Again, limited published evidence for the benefit relative to the safety of these invasive therapies has led the authors of current guidelines to advise reserving this therapy for children with progressive and severe disease who have failed optimal medical management. As research focused on childhood cerebrovascular disease continues to grow rapidly, the future prospects are good for improving knowledge of this disorder, and for growing the evidence basis for treatment.